KARIR PLATEAU DAN INTENSI BERWIRAUSAHA (KAJIAN EMPIRIS) - Made Wahyu Adhiputra (LPPM Universitas Dhyana Pura, 2018)
ABSTRACTThis study examined the antecedents and consequence of career plateau. Antecedents of career plateau are job tenure, age, job involvement and supervisor’s support. The consequence of career plateau is organizational commitment. Organizational commitment has three dimensions, namely affective organizational commitment, continuance organizational commitment and normative organizational commitment. This paper is a theorical and empirical analysis. Intense competition graduates of the intelectual is not matched by the number of jobs available, it will increase the number of unemployed intellectuals or educated unemployed college graduates. Entreprenuer attitude, motivation to comply, self efficacy is seen as an appropriate container for growing spirit to entrepreneurial behavior.Key Words: Career Plateau, Entrepreneurial Intentions